ANALISIS MODIFIKASI LEADING EDGE HULL VANE TIPE NACA 4421 TERHADAP HAMBATAN KAPAL MENGGUNAKAN METODE CFD - Rifki Rafi (2023)
The advancement of modern times has led to many desired accomplishments. One aspect that is needed is a ship with high speed and low resistance. The addition of an Energy Saving Device (ESD) to the ship is one form of application to reduce resistance in ship technology. Recently, the hull vane, as an underwater foil installed at the stern of the ship, has also been introduced to the shipping industry as an ESD. To achieve good aerodynamic performance on the airfoil, one of the methods is to shape the airfoil to mimic the shape of a humpback whale's flipper, known as tubercles. This research involves modifying the leading edge of the hull vane foil, NACA 4412 type, on the DTMB 5415 ship. Starting with the modeling of the hull of the DTMB 5415 model ship, modifications to the leading edge of the NACA 4412 type hull vane are made at various angles of attack, namely 3° and 7°, with a vertical placement distance of 40 mm from the trailing edge to the draft and a horizontal distance of 85 mm from the trailing edge to the after perpendicular. Calculations and analyses are conducted using the CFD method to assess the resistance components for the ship and the hydrodynamic efficiency of the NACA 4412 type. The results of the CFD analysis for all variations will be compared regarding their total resistance component effects, and conclusions will be drawn based on the simulation results. The model with a leading edge modification at a 3° angle of attack (Hv-M03) is found to have the smallest total resistance component, while the NACA model (Nc-M03) has the highest hydrodynamic efficiency.